2007
DOI: 10.1002/dc.20594
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical study of the expression of mesothelin in fine‐needle aspiration biopsy specimens of pancreatic adenocarcinoma

Abstract: Mesothelin is a potential marker of pancreatic adenocarcinoma that was recently identified by serial analysis of gene expression. We evaluated the sensitivity and specificity of mesothelin as a marker of pancreatic adenocarcinoma on destained Papanicolaou (Pap) smears and unstained cellblocks from 28 patients using a monoclonal antibody to mesothelin. Intensity and proportion of staining was semiquantitatively graded on a scale of 1-3, and as 0%, 1 to <10%, 10-50%, or >50%. Positive staining for mesothelin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Fourth, most of the IHC diagnostic biomarkers have been investigated individually [32,46,47,55,56], with few studies reporting the utility of biomarker panels [30,36]. We carefully selected candidate biomarkers reported in different studies (KOC, mesothelin, S100P and MUC1) for investigation in a single experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, most of the IHC diagnostic biomarkers have been investigated individually [32,46,47,55,56], with few studies reporting the utility of biomarker panels [30,36]. We carefully selected candidate biomarkers reported in different studies (KOC, mesothelin, S100P and MUC1) for investigation in a single experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a number of attempts have been made to improve the accuracy of cytology for pancreatic lesions . The level of S100P expression has been found to increase during the progression from PanIN to invasive adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…All the other four proteins have been observed to be variously overexpressed in pancreatic ductal carcinoma using histologic specimen . Few studies evaluated PSCA and/or mesothelin in FNA cytology specimen and showed increased accuracy in cytologically borderline cases . Baruch et al noted that the overall sensitivity and specificity of mesothelin were 68% and 90%, respectively and that the role of mesothelin alone as a marker for cytologic confirmation of pancreatic adenocarcinoma is limited by its rare expression in benign tissue, especially gastric epithelium that is a common source of contamination and frequent cause of pitfalls in EUS‐FNA pancreas specimens, as well as focal expression in malignant pancreatic tissue .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have also reported the usefulness of immunostaining of S100P,[ 246 279 280 281 282 283 284 285 ] mesothelin,[ 285 286 287 288 289 290 ] mucins,[ 287 291 292 293 294 295 ] or KOC/IMP3[ 279 282 296 297 298 ] in EUS-FNA samples. Those reports might help improve the efficacy of EUS-FNA for diagnosis of solid pancreatic masses.…”
Section: Going Beyond Cytological Diagnosismentioning
confidence: 99%